2024
DOI: 10.1186/s12909-024-05494-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in learning and study strategies impact medical students’ preclinical and USMLE step 1 examination performance

Sparsha Saxena,
William S Wright,
Mohammed K. Khalil

Abstract: Background Evaluation of students’ learning strategies can enhance academic support. Few studies have investigated differences in learning strategies between male and female students as well as their impact on United States Medical Licensing Examination® (USMLE) Step 1 and preclinical performance. Methods The Learning and Study Strategies Inventory (LASSI) was administered to the classes of 2019–2024 (female (n = 350) and male (n = 262)). Students’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have shown discrepancies in language learning and language-related skills between males and females. In order to mitigate any potential biases, we implemented gender correction techniques, which encompassed statistical adjustments to accommodate these gender variations [ 20 – 22 ]. The questionnaire was distributed and collected using the Wenjuanxing platform (Changsha Ran Xing Science and Technology, Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown discrepancies in language learning and language-related skills between males and females. In order to mitigate any potential biases, we implemented gender correction techniques, which encompassed statistical adjustments to accommodate these gender variations [ 20 – 22 ]. The questionnaire was distributed and collected using the Wenjuanxing platform (Changsha Ran Xing Science and Technology, Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%